Growth enhancement and drought tolerance of hybrid poplar upon inoculation with endophyte consortia - Khan, Zareen (2016)
With increasing effects of global climate change, there is a strong interest in developing biofuels from trees such as poplar (Populus sp.) that have high C sequestration rates and relatively low chemical inputs. Using plant-microbe symbiosis to maximize plant growth and increase host stress tolerance may play an important role in improving the economic viability and environmental sustainability of poplar as a feedstock. Based on our previous research, a total of ten endophyte strains were selected as a consortium to investigate the effects of inoculation on commercial hardwood cuttings of Populus deltoides x P. nigra clone OP-367. After one and a half months of growth under non-stress conditions followed by one month under water stress, there was substantial growth promotion with improved leaf physiology of poplar plants in response to the endophyte inoculation. Furthermore, inoculated plants demonstrated reduced damage by reactive oxygen species (ROS) indicating a possible mechanism for symbiosis-mediated drought tolerance. Production of important phytohormones by these endophytes and identification of microbial genes involved in conferring drought tolerance suggests their potential roles in the modulation of the plant host stress response.